THE SIGNIFICANCE OF THE SCIENTIFIC WORKS OF THE FAMOUS KYRGYZ ETHNOGRA- PHER, PROFESSOR A. ASANKANOV IN THE FORMATION OF THE CONCEPT OF THE KYRGYZSTANI (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Among a number of people who distinguished themselves by their worthy work in the history of Kyrgyzstan, the name of Doctor of Historical Sciences, Professor Abylabek Asankanov takes its place. Having worked fruitfully in the field of higher education in our republic for many years, he managed to create works. which lead to the history of Kyrgyzstan. As a result of his ethnographic data and scientific research over half a century of work, Professor A. Asankanov developed a concept for the development of self-identification of citizens by Kyrgyzstanis in the Kyrgyz Republic for 2021-2026. Our article examines the historical significance of the concept and its role in Kyrgyz society.
Keywords: Kyrgyzstani, concept, ethnography, ethnology, knowledge, culture, methodology